العوائق والحلول المتعلقة بتطبيق الحدود في المحاكم الشرعية في شمال نيجيريا: Obstacles and Solutions to Enforcement of Hudud in Shariah Courts in Northern Nigeria - أحمد عمر أحمد; عبد الصمد موسي (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص يهدف هذا البحث إلى دراسة العوائق والحلول المتعلقة بتطبيق الحدود في المحاكم الشرعية في شمال نيجيريا؛ وذلك لوجود العديد من المشاكل حال تطبيق الحدود في المحاكم الشرعية من ذلك التعارض الحاصل بين الدستور الفدرالي ودستور الولايات وخاصةً فيما يتعلق بتطبيق حد السرقة. فقام الباحث بدراسة الحدود الشرعية بشكل عام من حيث تعريفها لغةً وشرعاً مع ذكر أنواعها مع التطرق للتطبيق العملي للحدود الشرعية في المحاكم الشرعية في بعض الولايات الشمالية التي تم اختيارها كنموذج من هذه الولايات ولاية زمفرا، جيغاوا، كانوا، كادونا، كاتسينا وولاية بوتشي. كما تطرق للنظام القانوني والمحاكم في نيجيريا بشكل عام والنظام القانوني والمحاكم الشرعية في شمال نيجيريا بشكل خاص، وقد تم التطرق أيضاً لقوانين العقوبات الإسلامية التابعة لولايات زمفرا، كانوا بوتشي، جيغاوا. وقد استخدم الباحث منهجين من مناهج البحث العلمي منها: المنهج النظري الاستقرائي؛ حيث قام بدراسة موضوع الحدود عموماً وحد السرقة خصوصاً في المدونات الفقهية، إضافةً إلى الكتب، والدراسات والرسائل والمقالات العلمية، والوثائق والتقارير القانونية والشرعية التي كتبت في هذا المجال وتم تخزينها في المكتبات ومواقع الشبكات العنكبوتية وغيرها من مصادر المعلمومات. واستخدم الباحث أيضاً المنهج التطبيقي التحليلي؛ حيث قام بدراسة القضايا المتعلقة بالحدود والتي تم تطبيقها في المحاكم الشرعية في شمال نيجيريا، وخاصةً ما يتعلق بحد السرقة، ودراسة العوائق في تطبيق هذه الحدود من أجل إيجاد الحلول المناسبة لها. وقد توصل الباحث إلى جملة من النتائج من بينها أن الشريعة الإسلامية هي النظام الأمثل الذي يبنغي تطبيقه للحصول على السعادة الدائمة في الدنيا والآخرة. كما أن تطبيق الحدود الشرعية يساهم بشكل فعَّال في القضاء على الجرائم الواقعة والمنتشرة في المجتمع النيجيري وبالأخص الجهات الشمالية. من ضمن النتائج التي توصل إليها البحث توافق القانون الجنائي الإسلامي مع الفقه الإسلامي في أغلب الجوانب، وتوافق تطبيقات المحاكم الشرعية مع الشريعة الإسلامية في كثير من القضايا. يوصي الباحث المسؤولين بالقيام بجميع الحلول المذكورة في الدراسة ليتمكنوا من تطبيق الشريعة وتنفيذ الحدود الشرعية بشكل أفضل. كما يوصيهم أيضاً بضرورة تطوير القانون الجنائي الإسلامي ليتوافق بشكل كلي مع الشريعة الإسلامي، وضرورة تنفيذ جميع الأحكام الصادرة من قبل المحاكم الشرعية. Abstract This research aims to study the obstacles and solutions related to the application of hudud in Sharia courts in northern Nigeria; This is due to the presence of many problems when applying the hudud in Sharia courts, such as the conflict between the Federal Constitution and the Constitution of the States, especially with regard to the application of the had for theft. The researcher studied the Shariah hudud in general in terms of defining them linguistically and legally, with mentioning their types, while addressing the practical application of Shariah hudud in the Shariah courts in some northern states that were chosen as a model, these states are: Zamfara, Jigawa, Kan, Kaduna, Katsina and Bauchi states.The researcher also touched on the legal system and courts in Nigeria in general and the legal system and Sharia courts in northern Nigeria in particular, and the Islamic penal laws of the states of Zamfara, Kanbuchi and Jigawa were also discussed. The researcher used two scientific research methodologies, including: the inductive theoretical method; where he studied the subject of borders in general and the hudud of theft, especially in jurisprudence blogs, in addition to books, studies, letters, scientific articles, reports and legal documents that were written in this field and stored in libraries, websites and other sources of information. The researcher also used the applied analytical method; Where he studied the issues related to the hudud that were applied in the Sharia courts in northern Nigeria, especially with regard to the hudud of theft, and the study of the obstacles in the application of these hudud in order to find appropriate solutions to them. The researcher reached a number of results, including that Islamic Sharia is the optimal system that should be applied to obtain permanent happiness in this world and the hereafter. The application of legal borders effectively contributes to the elimination of crimes committed and prevalent in Nigerian society, especially in the northern regions. Among the findings of the research, the compatibility of Islamic criminal law with Islamic jurisprudence in most aspects, and the compatibility of the applications of Sharia courts with Islamic law in many cases. The researcher recommends the officials to carry out all the solutions mentioned in the study so that they can better apply the Sharia and implement the Sharia hudud. He also recommends to them the necessity of developing Islamic criminal law to be fully compatible with Islamic law, and the necessity of implementing all judgments issued by Sharia courts.